On the diminution of the national wealth from cattle diseases - Baldwin, Thomas (Statistical and Social Inquiry Society of Ireland, 1870)
In 1869 we had in Ireland 542,758 horses; 3,531,154 cattle; 4,141,280 sheep, and 1,157,734 pigs. The gross value of these was upwards of #50,000,000. The question I propose to submit for the consideration of the Society this evening is the proportion of this which was wasted by disease. The subject is very comprehensive; so much so, that I find I cannot adequately discuss it in one paper. Up to the present no attempt has been made to put even an approximately correct estimate of the loss before the public.
Read Tuesday, 15th February, 1870
Keywords: Cattle plague; Disease control; 314.15